Trinidad. Drying Cocoa - (:unkn) unknown (My University, 2010)
A picture of a group of workers beginning the process of spreading the cocoa beans on a cocoa house and on the side of the cocoa house donkeys with baskets full of cocoa pods strapped to their backs.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cocoa--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Cocoa trade--Trinidad and Tobago; Cocoa processing--Trinidad and Tobago; Working class--Trinidad and Tobago; 1905; Cocoa houses